Infrared based dry blanching and hybrid drying of bitter gourd slices: Process efficiency evaluation. (15th January 2018) - Nalawade, Sagar A.; Sinha, Akanksha; Hebbar, H. Umesh
Abstract: In the present study, combination of infrared (IR) based dry blanching and hybrid drying involving IR‐hot air was used for bitter gourd slices. Infrared blanching conditions were standardized based on the degree of enzyme (peroxidase and polyphenol oxidase) inactivation and product quality. The performance of IR blanching was compared with microwave (MW), water, and steam blanching. The performance of hybrid drying was compared to that of hot air (HA) drying. Microwave and IR blanched slices retained higher amount of ascorbic acid (95% and 93%, respectively) and charantin (76.8% and 74.8%), as compared to water and steam blanching. Infrared blanching followed by hybrid drying required ∼66% lesser time than water blanched‐HA dried with higher retention of charantin (68.4%), ascorbic acid (86.3%), and chlorophyll (42.9%), also consuming 79% less energy than HA drying. The results showed that IR‐based blanching and hybrid drying could be used effectively to produce dried bitter gourd slices having better quality. Practical applications: Bitter gourd ( Momordica charantia L.) is a good source of ascorbic acid and charantin. This study explored the potentials of infrared assisted blanching and hybrid drying of bitter gourd slices as an alternative to wet blanching (water & steam) and hot air drying. The infrared (IR) assisted blanching and hybrid drying employed in the present study resulted in shorter processing time with higher nutrient retention and higher energy efficiency than HA drying. The results indicated that IR assisted blanching and hybrid drying techniques have great industrial potential to reduce processing time as well as energy, besides producing the better quality product.